Extended-Hours Hemodialysis Without Dietary Restrictions Reduces Risk of Vascular Calcification - Kaneda, Hiroshi; Nishiyama, Toshiro; Owada, Kazunori; Katayose, Koichi; Takagi, Yutaka; Suzuki, Katsuhiko; Kaneda, Fumika (Journal of Medical Cases, 2025)
Vascular calcification is common in dialysis patients and is severely associated with cardiovascular morbidity and mortality. They have mineral metabolism disorders, which are considered to promote vascular calcification. In addition, hypertension and malnutrition, both prevalent in dialysis patients, are also considered risk factors contributing to vascular calcification. Our clinic has implemented extended-hours hemodialysis without dietary restrictions to solve the problems of hypertension and malnutrition in dialysis patients. We report a case where aortic calcification was slight despite 34 years of long-term dialysis. He underwent his first computed tomography (CT) scan of the chest and abdomen 29 years after initiating hemodialysis to evaluate his kidney transplant. The abdominal aortic calcification index 29 years after initiating dialysis was low at 5.8%, and even after 5 years, it was only 6.7%. The coronary artery calcification score was moderate at 214.0, but the degree of vascular calcification appeared milder than in conventional dialysis patients. His dialysis modality is unique. He began extended-hours hemodialysis without dietary restrictions 1.5 years after his transfer to our clinic, extending his dialysis time to 6 h. He gradually increased it to 10 h, and the dietary restriction was significantly relaxed. Moreover, he has been undergoing this treatment for about 26 years. His muscle mass increased, and his nutritional status remained adequate. The mean serum phosphorus and calcium levels were within the normal range (5.4 ± 0.5 mg/dL and 8.8 ± 0.3 mg/dL), and the calcium-based phosphate binder was successfully reduced and eventually discontinued. Furthermore, the blood pressure normalized without the use of antihypertensive medications. These may have removed some of the risk factors for vascular calcification. Recent studies suggest that extended-hours hemodialysis without dietary restrictions significantly lowers calciprotein particle levels, a risk factor for vascular calcification, compared to conventional dialysis. In conclusion, extended-hours hemodialysis without dietary restrictions may reduce the risk of vascular calcification by improving control of malnutrition, hypertension, and mineral metabolism.